Adverse Events Following Immunization of mRNA and Inactivated Vaccines Against COVID-19 at Universitas Indonesia Hospital: A Cross-Sectional Study - Vriona Ade Maenkar; Retnosari Andrajati; Nadia Farhanah Syafhan (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Background: The coronavirus that causes severe acute respiratory syndrome (COVID-19) is coronavirus 2 (SARS-CoV- 2). This virus has caused a global pandemic. The adverse impact of this virus in the past two years has resulted in efforts to build herd immunity through vaccination. This study aimed to identify the side effects after getting the Pfizer and Sinovac vaccines at the Universitas Indonesia Hospital and the risk factors for Adverse Events Following Immunization (AEFI).Methods: This observational study used a descriptive, non-experimental method with a cross-sectional design. Google Forms was used to collect data.Results: The onset of AEFI symptoms ranged from 15 minutes to 24 hours. The common AEFI symptoms were pain at the injection site, fatigue, muscle aches, and joint pain. The AEFI severity was mostly at the mild level, and only a few participants took medication. Female participants, participants with comorbidities and allergies, previous medication histories within the last 6 months, and those with experience of COVID-19 had a higher risk for AEFI with a statistically significant effect (P <0.005).Conclusion: This study revealed that Pfizer and Sinovac COVID-19 vaccines were safe to administer as the AEFIs were mostly mild and automatically disappeared and decreased after 1 to 3 days.